2016
DOI: 10.1111/irv.12430
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B virus outbreak at a religious residential school for boys in Northern Bangladesh, 2011

Abstract: BackgroundNational media reported a febrile illness among dormitory residents of a boys' religious school. We investigated the outbreak to identify cause.MethodsIndividuals with fever (>100°F) and cough or sore throat between 1 and 13 August 2011 were influenza‐like‐illness (ILI) case‐patients. We collected histories and specimens from hospitalized case‐patients and visited campus to explore environmental context.ResultsAll 28 case‐patients were dormitory residents including 27 hospitalizations. Accommodation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Another enormous and highly significant group of children and adolescents are enrolled to Islamic boarding schools or pesantren. Several studies already proved the role of pesantren in relation with immunization and the transmission of some infectious diseases (Haque et al, 2017;Pratama, Putri, Wibowo, & Nugraheni, 2016;Sumarni & Susanna, 2014).…”
Section: The Limitation Of the Studymentioning
confidence: 99%
“…Another enormous and highly significant group of children and adolescents are enrolled to Islamic boarding schools or pesantren. Several studies already proved the role of pesantren in relation with immunization and the transmission of some infectious diseases (Haque et al, 2017;Pratama, Putri, Wibowo, & Nugraheni, 2016;Sumarni & Susanna, 2014).…”
Section: The Limitation Of the Studymentioning
confidence: 99%
“…Fieldworkers again observed hygiene practices 14 months after the pilot intervention commenced. Out of 230 students' coughing and sneezing events, 13 (6%) students used their upper sleeves after coughing (5) and after sneezing (8), and 4 (2%) covered their coughs and sneezes with a dopatta (scarf). However, 154 (67%) students coughed and sneezed into the open air, and 59 (26%) covered their coughs and sneezes with hands and did not wash them with water and soap afterward (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Schools are efficient settings for the spread of infectious respiratory diseases, facilitating outbreaks and expanding epidemics by bringing many individuals together in a limited area for prolonged periods. [1][2][3][4] Studies conducted both in high-and low-income countries including Bangladesh 5 suggested that close proximity interaction in schools and within students' social network enhances the transmission of infectious disease, particularly influenza, in schools, households, and communities. [6][7][8][9][10][11][12][13][14][15] Focused research on coughing and sneezing behaviors and habits, however, has been rare.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza outbreaks are not new in crowded environments such as schools [ 8 10 ]. Outbreak of influenza in these and many other settings could easily go undetected or in some cases unreported.…”
Section: Discussionmentioning
confidence: 99%